Formation of high ultraviolet transparent SrVOx/Ag-based conducting electrode. Issue 11 (1st August 2020) - Kim, Su-Kyung; Cho, Jin-Woo; Im, Hyeong-Seop; Lim, Weon-Cheol; Kim, Sun-Kyung; Seong, Tae-Yeon
Abstract: Sputter-deposited SrVOx was employed to create transparent conducting SrVOx /Ag/SrVOx films and their optical-electrical properties were examined as functions of SrVOx and Ag thicknesses. With the increase in the thickness of SrVOx films from 15 to 45 nm in the SrVOx /Ag/SrVOx films, the carrier concentration, sheet resistance, and electron mobility were in the range of 2.0 × 10 22 − 1.03 × 10 22  cm −3, 3.15−2.76 Ω/sq., and 21.99−19.76 cm 2 /Vs, respectively. The 25 nm-thick SrVOx -based multilayer gave the highest average transmittance ( T av ) of 91.5%. The 25 nm-thick SrVOx -based multilayer gave the largest Haacke's figure of merit (FOM) of 144.5 × 10 −3  Ω −1 . With increasing Ag layer thickness from 9 to 21 nm, the carrier concentration, mobility and sheet resistance of the multilayers were in the range of 1.05 × 10 22 − 1.99 × 10 22  cm −3, 15.56−22.46 cm 2 /Vs, and 1.97−6.48 Ω/sq., respectively. The T av of the SrVOx (25 nm)/Ag/SrVOx (25 nm) multilayer gradually decreased from 95.5 to 82.6% with the Ag layer thickness. The rigorous coupled-wave (RCW) simulations were performed to describe the wavelength-dependent transmittance characteristics of the SrVOx (25 nm)/Ag (15 nm)/SrVOx (25 nm) samples. Based on the phasor examination, the effect of the SrVOx film thickness on the transmittance characteristics of the multilayers is described and discussed.